Effects of applying a training program on basketball shooting in young players - Ferraz, R.; Marques, M. C.; Branquinho, L.; Marinho, D. A. (Journal of Human Sport & Exercise, 2021)
The main aim of this study was to determine the effects of the application of a strength program in the accuracy of basketball shooting in young female players. Twenty female basketball players, (mean ± standard deviation: 12.08 ± 0.42 years; 1.55 ± 0.08 height; 44.4 ± 5.54 body mass) participated in the study. The participants were divided into two groups, the Control Group (GC) and the Experimental Group (GE), and were evaluated in 4 throwing exercises before (Pre-Test), after the application of a 6-week strength program (Post-Test), as well as after 4 weeks of detraining. The applied training program includes four exercises: i) Jump with Counter-Movement; ii) Throwing of the Medicinal Ball; iii) Sit-ups; iv) Push-ups. The results suggest that application of the 6-week training program had a positive effect on performance in two the four throwing exercises. In addiction 4 weeks of detraining, did not cause significant changes in the performance of the different throwing exercises compared to the Post-test period. It was concluded that a strength training program with a duration of 6 weeks was sufficient to obtain positive effects in the effectiveness of 2 Point throwing exercises in young female basketball players.